2017
DOI: 10.1097/md.0000000000007205
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of HLA-DP/DQ polymorphisms with transplant etiologies and prognosis in liver transplant recipients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
2
0
3
Order By: Relevance
“…Other studies showed that rs7453920 and rs7768538 are associated with persistent HBV infection and HCC development. 31 , 32 In addition, Li et al 33 discovered that rs7453920 was related to the prognosis of liver transplant recipients. The exact mechanism by which gene polymorphisms in HLA-DRB1 and HLA-DQB2 affect the clinical outcome of patients with HBV-related HCC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that rs7453920 and rs7768538 are associated with persistent HBV infection and HCC development. 31 , 32 In addition, Li et al 33 discovered that rs7453920 was related to the prognosis of liver transplant recipients. The exact mechanism by which gene polymorphisms in HLA-DRB1 and HLA-DQB2 affect the clinical outcome of patients with HBV-related HCC is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Xu et al showed that the rs7453920G allele was a risk factor for HBV infection, while rs7453920A allele served as a protective factor in chronic Hepatitis C [ 26 ]. Furthermore, rs7453920A allele could predict the better prognosis in liver transplant recipients, and was associated with decreased risk of ankylosing spondylitis (AS) [ 27 ]. The explanation of this could be that HBV and HCV have remarkable differences in the molecular virology and specific immune responses, although both of them are hepatotrophic factors and tend to produce liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Với rs3077, tỉ lệ alen A ở nhóm bệnh là 0,281 theo nghiên cứu của Yi Li (2017). 12 Theo tính toán, cỡ mẫu tối thiểu cho nghiên cứu về rs3077 là 78.…”
Section: Phương Phápunclassified
“…GG là 53%. 12,15 Nghiên cứu của chúng tôi chưa tìm thấy Nghiên cứu cũng đánh giá mối liên quan giữa rs3077 với một số đặc điểm lâm sàng của nhóm xơ gan (bảng 3). Tuy nhiên, khi so sánh sự phân bố các kiểu gen trong các nhóm chia theo giới tính, độ tuổi (≤ 60, > 60), chỉ số Child Pugh (A, B, C) đều không tìm thấy sự khác biệt có ý nghĩa thống kê (p > 0,05).…”
Section: Phương Phápunclassified
See 1 more Smart Citation